2016
DOI: 10.1534/g3.116.027706
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Genome Editing in Chicken DF-1 Cells Using the CRISPR/Cas9 System

Abstract: In recent years, genome engineering technology has provided unprecedented opportunities for site-specific modification of biological genomes. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) 9 is one such means that can target a specific genome locus. It has been applied in human cells and many other organisms. Meanwhile, to efficiently enrich targeted cells, several surrogate systems have also been developed. However, very limited information exists on the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
(66 reference statements)
2
22
0
1
Order By: Relevance
“…Thus, all used methodological approaches confirmed the correct-ness and effectiveness of the transgene integration. [Bai et al, 2016]. The low effectivity in our case can be explained by several reasons: we were restricted by 50-100 bp sequence of genomic DNA for selection of gRNAs; the area of targeting is the beginning of 3'UTR, which usually has a lower GC content and has a lot of repeated elements; also the transfection efficiency of the DF1 cells with multiple plasmids was less than 50%.…”
Section: Enrichment Of Successfully Edited Cells With Geneticin Selecmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, all used methodological approaches confirmed the correct-ness and effectiveness of the transgene integration. [Bai et al, 2016]. The low effectivity in our case can be explained by several reasons: we were restricted by 50-100 bp sequence of genomic DNA for selection of gRNAs; the area of targeting is the beginning of 3'UTR, which usually has a lower GC content and has a lot of repeated elements; also the transfection efficiency of the DF1 cells with multiple plasmids was less than 50%.…”
Section: Enrichment Of Successfully Edited Cells With Geneticin Selecmentioning
confidence: 85%
“…We used human codon-optimized Cas9 (hCas9) as it has been previously demonstrated that the optimized Cas9 works in chicken cells and there was no need to synthesize chicken codonoptimized nuclease [Bai et al, 2016 Unique 20bp sequences for the selected gRNAs were cloned under human U6 promoter in the plasmid phU6-gRNA (#53188, Addgene). A plasmid pQE30TaqRFP (Evrogen; Moscow, Russia) coding RFP was used for cotransfection as a reporter of the efficiency of DNA delivery to the cells.…”
Section: Construction Of Expression Vectorsmentioning
confidence: 99%
“…Early attempts at implementation in avian embryos employed a tetracycline-inducible Cas9 system to perform gene editing of Pax7 using Tol-2 mediated integration at stages after neural tube closure (Véron et al, 2015). While useful, this approach functioned at low efficiency, particularly at early developmental stages (Bai et al, 2016; Oishi et al, 2016; Véron et al, 2015). Since then, several studies performed in other model systems have reported optimizations of individual CRISPR/Cas9 components, improving our understanding of this gene-editing technology (Chen et al, 2013; Doench et al, 2016; Gandhi et al, 2017; Port et al, 2014; Ren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This surrogate system was based on using the puromycin resistance gene and EGFP as double reporter genes to enrich cells with mutations induced by CRISPR/Cas9 nucleases in the human and chicken genomes. In contrast, the mutation frequency of chicken PPAR-γ was 60.7% under puromycin selection; however, only a 0.75% mutation efficiency was detected without puromycin selection [15]. Based on this finding, we directly used this reporter system to enrich cells with targeted mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient gene disruptions of PPAR-γ , ATP5E and OVA were obtained in chicken somatic cells DF-1 with an enrichment system [15]. Véron et al .…”
Section: Introductionmentioning
confidence: 99%